2020
DOI: 10.1111/dth.14333
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between the effect of topical tazarotene 0.1 gel alone vs its combination with tioconazole nail paint in treatment of onychomycosis

Abstract: Onychomycosis (OM) is a chronic fungal infection of the nail caused by dermatophytes, yeasts, and nondermatophytes. Tioconazole is one of the topical antifungal belonging to imidazole derivatives. Tazarotene is a synthetic retinoid, with immunomodulating properties and anti-inflammatory activity. To evaluate the efficacy of tazarotene 0.1% gel alone in comparison with its combination with tioconazole nail paint in the treatment of onychomycosis. Forty patients presented with onychomycosis, subjected to a full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Our results agreed with a previous study, in which the fingernail infection was the most frequent in OM infection, with fingernails and toenails being involved in 67 percent and 33 percent of patients, respectively [7]. As well, another study announced that fingernails (37.5%) were found to be more common than toenails (12.5%) in OM patients [8]. Our findings contradicted a previous study, which found that nails in the toes are more common than nails in the fingers [9].…”
Section: Discussionsupporting
confidence: 92%
“…Our results agreed with a previous study, in which the fingernail infection was the most frequent in OM infection, with fingernails and toenails being involved in 67 percent and 33 percent of patients, respectively [7]. As well, another study announced that fingernails (37.5%) were found to be more common than toenails (12.5%) in OM patients [8]. Our findings contradicted a previous study, which found that nails in the toes are more common than nails in the fingers [9].…”
Section: Discussionsupporting
confidence: 92%
“…Onychomycosis (OM) is a chronic fungal infection of the nail caused by dermatophytes, yeasts, and non-dermatophytes. El-Salam et al [32] evaluated the efficacy of tazarotene 0.1% gel alone or combined with tioconazole nail paint in the treatment of onychomycosis due to Aspergillus spp., including A, candidius, A. flavus, A. niger, A. nidulans and A. terreus [32]. Forty patients presenting with onychomycosis underwent full history taking, as well as clinical and nail examination, including a clinical and dermoscopic assessment of severity using the Onychomycosis Severity Index (OSI), KOH test, and fungal culture.…”
Section: Effectiveness Of Retinoids Against Environmental Humanmentioning
confidence: 99%
“…A significant treatment response was found in those patients treated with tazarotene 0.1% gel administered in combination with tioconazole, compared to tazarotene 0.1% gel alone (decrease in OSI, dermoscopic features, and mycological clearance). Tazarotene alone has been shown to have an antifungal activity especially against Aspergillus niger and A. flavus, whereas, when combined with antifungals such as tioconazole, it seems to be more effective, suggesting its potential use as adjuvant for standard systemic or topical antifungal treatments of onychomycosis [32]. Based on the immunomodulatory activity of retinoids and given that the nail unit is an immunological niche, a balance between pro-inflammatory and anti-inflammatory cytokines is paramount for the correct management of onychomycosis and other related inflammatory diseases such as psoriasis [33].…”
Section: Effectiveness Of Retinoids Against Environmental Humanmentioning
confidence: 99%
“…Disk diffusion assay after 48 h of incubation in tazarotene solution showed a central area of inhibition in all in vitro fungal cultures [32]. In a comparative cross-sectional study of 40 patients, clinical improvement as assessed by the onychomycosis severity index was 25% in patients treated with tazarotene alone, compared to 50% in patients treated with tazarotene and tioconazole ( p = 0.039) after 3 months of therapy [33]. In a clinical trial of 102 patients treated with fractional carbon dioxide laser-assisted delivery of topical tazarotene or topical tioconazole, there was no difference in clinical cure between groups ( p = 0.33).…”
Section: Introductionmentioning
confidence: 99%